Keanggotaan Indonesia dalam BRICS: Antara Ketahanan Ekonomi dan Kerentanan Struktural - Aswin Ariyanto Azis; Muhammad Irfan Azhari; Nisriinaa Alyaa; Laura Ayako Suryawarman; Roy Erza Faraby; Hassya Talitha Nur Mahsa; Arief Rahman Maulana (Jurnal Ilmiah Hubungan Internasional, 2026)
Indonesia's decision to join BRICS in 2025 represents a significant foreign policy maneuver. This has generated both optimism and concern, particularly regarding its implications for national economic stability amidst the dynamics of rivalry between Western and non-Western powers. Current studies are limited to the locus of Indonesia's geopolitical strategy or diplomatic approach to BRICS, while readiness approaches to Indonesia's structural economic for deeper integration with BRICS are still relatively minimal. The absence of analyses that systematically assess Indonesia's economic vulnerability and resilience within BRICS membership constitutes a key research gap in this study. Methodologically, this study employs qualitative analysis through literature review, analysis on relevant statistical data, and triangulation with expert interviews from the Indonesian Ministry of Foreign Affairs to deeply examine Indonesia's structural capacity. The findings indicate that Indonesia exhibits relatively strong economic resilience, while simultaneously facing moderate but structural economic vulnerability due to asymmetric economic relationships and high potential dependency with key partners. Consequently, the BRICS membership benefits for Indonesia depends primarily on domestic economic strengthening, ensuring that its membership enhances, rather than limits, national strategic autonomy. Thus, this article provides an evaluative framework to assess the economic implications of Indonesia's membership in BRICS in a measurable framework. Keywords: BRICS; Indonesia; economic vulnerability; economic resilience; foreign policy